Analysis of United States of America Foreign Policy on the Victory of the Taliban Group in Afghanistan - Rio Sundari; Wicaksono, Agung; Angeli, Fanesa; Prayuda, Rendi; Shiddiqy, M. Arsy Ash (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2024)
This research aims to discuss about analysis of United States foreign policy in Afghanistan by looking at case studies of the victory of the Taliban group controlling Afghanistan in 2021. Foreign policy is a unit of analysis in international relations that is related to the national political system. This strategy carried out in foreign policy lasts if the State interacts in the form of relations with the international community in making decisions to achieve its national goals. In making broad country decisions, there is a theory expressed by Richard Snyder which says there are internal factors and external factors that influence a country in determining foreign policy. In the case of the Taliban's victory over Afghanistan in 2021, the United States' policy in responding to the conflict explained the internal and external factors that influence each other. Internal factors are influenced by the structure and social behavior of the State, where this is influenced by the ideology of the State, existing government institutions in the State, where this is influenced by the ideology of the State, existing government institutions in the State, the characteristics contained in national organizational institutions and the role of social groups in influencing decision making which are internal factors. The existence of internal and external factors then provides the results of the decision-making process that cannot be separated from action in decision-making. The conclusion, internal factors and external factors that influence the direction of the United States foreign policy in dealing with cases of conflict in Afghanistan have an impact on the victory of the Taliban group in controlling Afghanistan in 2021.